Comparison of two morphotypes of Zuccagnia punctata (Fabaceae) from Valles Calchaquíes in Argentina - Álvarez, María A. (2023)
Zuccagnia punctata Cav. (Fabaceae) is a medicinal aromatic shrub, a monotypic species with a wide distribution in Argentina. Two morphotypes were found in Valles Calchaquíes, one with yellow fruits (YF) and other with red-brown fruits (RBF). The color of fruits varies between individuals within a population, with some plants producing red-brown fruits and other yellow fruits. The cytogenetic differentiation was determined using root tips. Leaves and fruits were used to analyze chemical composition by HPLC-DAD and HPLC/MS/MS. The number of chromosome (2n = 24) was reported for the first time for the genus. The yellow fruits and red-brown fruits morphotypes showed different karyotypes. The compounds common to both morphotypes were identified in leaves and fruits as chalcones, compounds with biological activity and biomarkers used for quality control of Z. punctata products. Two chemotypes related to the color of the fruits, were detected. An anthocyanin, cyanidin 3-glucoside was found in red-brown fruits (4.75 mg.g-1 fruits) but not in yellow fruits. These is the first report on yellow fruits morphotype of Z. punctata and on presence of anthocyanins in Z. punctata red-brown fruits morphotype. This work contributes to the knowledge of Z. punctata, a native plant from Argentina with high economic potential to promote the regional economy.